Homeownership affordability of low income group in Kuala Lumpur - Rameli, Norizan; Salleh, Dani; Ismail, Mazlan (2017)
The housing issue has taken over the global attention particularly homeownership affordability issue. Owning a house is significantly known as one of the basic necessities in human survival. Thus, the capability of the low income group to afford a house is practically the main highlight in this issue. Besides, the escalation of the low income group in the urban areas which occurred due to the migration to enhance a better life causes this issue to be left as a debatable one. Hence, it is important to identify the affordability levels and also the socioeconomic factors which affect the homeownerships affordability of the low income groups in Kuala Lumpur city. The socioeconomic factors were focused on household income, household expenditures, type of employments, the education levels, household sizes, the monthly payment for housing and the household savings. Furthermore, an investigation based on the stratified sampling techniques was carried out on a total of 400 of head households according to their specified residential zones. The indication of the housing affordability level was measured based on the residual income theory whereas the binary logistic regression was implemented in identifying their affordability factors. The results exhibit the low income groups are afforded to own public housing unit in Kuala Lumpur. Household income, household expenditures and monthly payment for housing affect homeownership affordability significantly. Conversely, education level, types of employment, household size and household savings not affects homeownership affordability significantly.